EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) MENGGUNAKAN METODE PEMECAHAN MASALAH DITINJAU DARI SIKAP KREATIF PESERTA DIDIK - Nurul Farida (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
The aim of the research was to determine the effect of learning models (STAD by problem solving method, STAD, and conventional) on mathematics achievement viewed from student creative attitude. The type of the research was a quasi experimental research. The population was the students in grade VIII junior high school in Central Lampung Regency. The conclusions of the research were as follows. (1) Students who taught by cooperative learning model of STAD by problem solving method type give better mathematics learning achievement than STAD type and conventional and then students who taught by cooperative learning model of STAD type give better mathematics learning achievement than conventional (2) For students who middle and low creative attitude, students who taught by cooperative learning model of STAD by problem solving method type give better mathematics learning achievement than STAD type and conventional and then students who taught by cooperative learning model of STAD type give better mathematics learning achievement than conventional.